First book of atas of the conselho de Tui some thoughts - Fernandez, Manuel Torres (Seven Editora, 2023)
Steeped in history, the border city of Tuy is witness to the great episodes of relations between Spain and Portugal, while it houses within the walls the social relations of the Old Regime, in a specific local variant typical of Galicia <of the late 16th century. and the beginning of the 17th century. In this way, the trade structured by the flow of the Miño River, the crafts organized through the guilds, the great calamities of the century such as the plague and, on the contrary, the festivals and popular celebrations. DOI: https://doi.org/10.56238/devopinterscie-018